Studies on Ottoman Palestine - Cohen, Amnon 1936- (Farnham, Surrey, England : Burlington, VT, USA : Ashgate Variorum, 2011)
These studies are based on Amnon Cohen's years of research in the archives of the Shari'a courts in Jerusalem, as well in Ankara and Istanbul, London and Paris. They are enhanced by travellers' reports, diplomatic correspondence, and Arab chronicles of the Middle East.
Includes bibliographical references and index.
Keywords: 638-1918; Palestine -- History -- 638-1917.; Turkey -- History -- Ottoman Empire, 1288-1918.; Middle East -- Palestine; Turkey; History